WHEN INTERNATIONAL CONTRACTS FOR THE SALE OF GOODS ARE TRAPS FOR BUSINESS PEOPLE - Wander, LA; Manna, JS (The journal of contemporary issues in business and government, 2007)
Sixty-eight nations, accounting for more than two thirds of global trade, follow international legal rules which govern contracts for the international sale of goods.1 In light of the recent trends in globalisation and liberalisation of international trade, business managers, previously accustomed to their own local or domestic laws, must deal with the perils and traps that arise from these international rules. Most of Europe, the United States, Russian Federation, Mexico, Australia, Canada and China have adopted the United Nations Convention on Contracts for the International Sale of Goods (CISG); an international agreement between these nations that embodies the new rules of international trade agreements involving the sale of goods.2 The CISG pre-empts a country's domestic law, including the Uniform Commercial Code (UCC) in the United States, which could present precarious results for business managers who are unaware of its existence (Mather, 2001).